Digital Marketing Training to Form the Entrepreneur Spirit of IPNU-IPPNU Members in Bondansari Village, Wiradesa District - Marotina, R. Nia (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
Bondansari Village has potential in agriculture. However, this potential has not been optimized because it is only managed by residents of Bondansari Village who are old enough many of them only sell natural products from their gardens offline, so it is still necessary to empower Human Resources (HR), especially young people, to shape their souls. Their entrepreneurs are expected to be able to optimize the potential that exists in Bondansari Village. This service aims to form the entrepreneurial spirit of IPNU-IPPNU members in Bondansari Village to increase the income of Nahdlatul Ulama students in developing the IPNU IPPNU organization and helping the family economy. This service is carried out in three stages: planning, implementation, and evaluation. 20 IPNU-IPPNU members from Bondansari Village attended this activity. The results of this dedication show that digital marketing can motivate IPNU-IPPNU members of Bondansari Village to become entrepreneurs.